Recent Advances and Clinical Outcomes of Kidney Transplantation Volume 2 - Cheungpasitporn, Wisit; Thongprayoon, Charat; Leeaphorn, Napat (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Advances in immunosuppression and kidney transplant techniques have led to significant improvements in the short-term survival of the renal allograft. Long-term graft survival, however, has relatively lagged behind and has now become one of the main problems in kidney transplantation. In this Special Issue, we discuss the recent research developments in kidney transplants that may affect long-term allografts, as well as the survival of the patient. The latest developments in living kidney donation are also explored.